Analysis of the Aedes albopictus C6/36 genome provides insight into cell line utility for viral propagation. Issue 3 (10th January 2018) - Miller, Jason R; Koren, Sergey; Dilley, Kari A; Puri, Vinita; Brown, David M; Harkins, Derek M; Thibaud-Nissen, Françoise; Rosen, Benjamin; Chen, Xiao-Guang; Tu, Zhijian; Sharakhov, Igor V; Sharakhova, Maria V; et al.
Abstract: Background: The 50-year-old Aedes albopictus C6/36 cell line is a resource for the detection, amplification, and analysis of mosquito-borne viruses including Zika, dengue, and chikungunya. The cell line is derived from an unknown number of larvae from an unspecified strain of Aedes albopictus mosquitoes. Toward improved utility of the cell line for research in virus transmission, we present an annotated assembly of the C6/36 genome. Results: The C6/36 genome assembly has the largest contig N50 (3.3 Mbp) of any mosquito assembly, presents the sequences of both haplotypes for most of the diploid genome, reveals independent null mutations in both alleles of the Dicer locus, and indicates a male-specific genome. Gene annotation was computed with publicly available mosquito transcript sequences. Gene expression data from cell line RNA sequence identified enrichment of growth-related pathways and conspicuous deficiency in aquaporins and inward rectifier K + channels. As a test of utility, RNA sequence data from Zika-infected cells were mapped to the C6/36 genome and transcriptome assemblies. Host subtraction reduced the data set by 89%, enabling faster characterization of nonhost reads. Conclusions: The C6/36 genome sequence and annotation should enable additional uses of the cell line to study arbovirus vector interactions and interventions aimed at restricting the spread of human disease.